The real Lincoln a new look at Abraham Lincoln, his agenda, and an unnecessary war - Di Lorenzo, Thomas J. (Forum, 2002)
Portrays the sixteenth president as a man who devoted his political career to revolutionizing the American form of government from one that was very limited in scope and highly decentrlized to a highly centralized, activist state.
Keywords: Lincoln, Abraham <1809-1865>; Lincoln, Abraham -- 1809-1865; Politik; USA; United States -- Politics and government -- 1861-1865